INCREASING STUDENTS' LEARNING MOTIVATION AT THE RUMAH DHUAFA AULIA FOUNDATION TO PREPARE SUPERIOR HUMAN RESOURCES FOR A GOLDEN INDONESIA 2045 - Agrasadya, Agrasadya; Latif, Latif; Sunarto, Ading (Yayasan Education and Social Center, 2024)
Education is an important form of long-term investment for a human being. Successful education will create people who are fit and worthy in society and will not cause trouble to other people. Societies from the most backward to the most advanced recognize that education or teachers are one of the many main elements that form the main prospective members of society. Successful education will create people who are fit and worthy in society, so it is important for education to produce people who are qualified and competitive. The method used in this community service activity is to provide training and socialization in order to build students' mindset and enthusiasm to increase students' learning motivation. The stages carried out in this activity are: Preparation stage and training stage. The results of community service obtained are increased motivation for participants at the Aulia Bojongsari Depok orphanage so that they are trained and increase their insight into the importance of learning for the future and building a golden generation in the future. It is hoped that the knowledge gained in this Community Service activity will be able to encourage new enthusiasm in delivering material and motivation, as well as contributing to the younger generation, especially participants from both elementary and middle and upper secondary levels, also with positive aims both in the business world, campus and family